Electrospinning of cotton-like fibers based on cerium-doped sol–gel bioactive glass - Lu, Hsuan-Heng; Zheng, Kai; Boccaccini, Aldo R.; Liverani, Liliana (Materials Letters, 2023)
In this study, Ce-doped calcium silicate-based bioactive glass sols were electrospun under well-defined parameters and heat-treated to obtain cotton-like fibrous structures. The 3D structures comprised long and entangled fibers with interconnected pores, and the successful incorporation of Ce was confirmed by EDX analysis. The fibers were highly hydrophilic and demonstrated in vitro bioactivity after immersion in simulated body fluid. The fibers were non-cytotoxic toward keratinocytes and did not inhibit the wound closure process, which was characterized in vitro.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Bioactive glass; Electrospinning; Fibers; Sol-gel; Wound healing